E-policy handbook : designing and implementing effective e-mail, internet, and software policies - Flynn, Nancy L. (American Management Association New YorkUS, 2000)
Aims to help employers to identify their organization's e-risks; and provides step-by-step guidelines for producing and implementing comprehensive, effective written e-mail, internet and software policies. Includes sample memoranda; questionnaires; software usage policies etc. Advises on topics including: conducting an internal audit; developing an effective e-risk management policy; establishing netiquette guidelines for managers and employes; and addressing employees electronic writing needs.